2005
DOI: 10.1002/nau.20182
|View full text |Cite
|
Sign up to set email alerts
|

A urodynamics protocol to optimally assess men with post‐prostatectomy incontinence

Abstract: The proposed urodynamic protocol allows for an optimal assessment of bladder and sphincter dysfunction and outlet obstruction in men with PPI.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
21
1
1

Year Published

2006
2006
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 55 publications
(23 citation statements)
references
References 22 publications
(24 reference statements)
0
21
1
1
Order By: Relevance
“…In the current study, the ALPP was measured without a urethral catheter because this method is believed to be more natural. 17,18 The correlation coefficient between the ALPP after RARP and ULR (r = -0.480, P < 0.001) was higher than that between MUCP after RARP and ULR (r = -0.409, P < 0.001) in the present study. MUCP is measured in the static state, and the ALPP is measured in the dynamic state with abdominal pressure.…”
Section: Commentcontrasting
confidence: 69%
“…In the current study, the ALPP was measured without a urethral catheter because this method is believed to be more natural. 17,18 The correlation coefficient between the ALPP after RARP and ULR (r = -0.480, P < 0.001) was higher than that between MUCP after RARP and ULR (r = -0.409, P < 0.001) in the present study. MUCP is measured in the static state, and the ALPP is measured in the dynamic state with abdominal pressure.…”
Section: Commentcontrasting
confidence: 69%
“…Each patient was evaluated with a history and physical examination, a voiding diary, and a 24-hr pad test. The diagnosis of stress incontinence was con¢rmed via video-urodynamics using our previously described protocol [Huckabay et al, 2005] and the standards of the International Continence Society [Abrams et al, 2002]. Patients were excluded if the primary etiology of their incontinence was detrusor overactivity.…”
Section: Methodsmentioning
confidence: 99%
“…Studies have suggested that the utmost common etiology in patients with persisting UI symptoms was sphincter incompetence (causing stress urinary incontinence-SUI). 6 There exists evidence, however, that sphincter incompetence can occur in conjunction with detrusor overactivity (DO), and also that DO with adequate sphincter function, low compliance, and urethral stricture are prevalent as the cause for UI or other LUT symptoms or dysfunction after radical prostatectomy. 7,8 The ICI-CDT recommends to perform complete UDS including cystometry and pressure flow analysis and PVR in patients with persisting incontinence or other LUT dysfunction following radical prostatectomy.…”
mentioning
confidence: 99%